Surgical Treatment for Laryngopharyngeal Reflux Disease - Nugraheni, Nugraheni; Aminah, Aminah (The Indonesian Journal of General Medicine, 2024)
Background: The surgical treatment of laryngopharyngeal reflux disease (LPRD) has evolved significantly over the years, reflecting advances in both surgical techniques and our understanding of the disease itself. Literature Review: Laparoscopic fundoplication has emerged as the preferred surgical method due to its favorable outcomes and lower complication rates compared to traditional open surgery (Liakakos et al., 2009). This minimally invasive approach not only effectively controls GERD symptoms but also enhances the quality of life for patients, including those with recalcitrant cases. The ongoing exploration of novel endoscopic techniques, such as endoluminal gastroplication, indicates a commitment to improving surgical options available for reflux management (Liakakos et al., 2009). Conclusion: In conclusion, the surgical treatment of LPRD requires a multifaceted approach that integrates advances in surgical techniques, patient-specific factors, and a robust understanding of the disease's pathophysiology. The interplay between surgical and medical management strategies is essential for optimizing patient outcomes and addressing the complexities associated with LPRD.